IMPLEMENTASI PROGRAM READ ALOUD UNTUK MENINGKATKAN LITERASI MEMBACA SISWA KELAS III MI LANTABURO KOTA TANGERANG - Fitria, Nurul; Miftachudin; Feny Nida Fitriyani (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Reading ability is one of the fundamental competencies that elementary school students must possess because it plays a crucial role in acquiring and understanding information. A good mastery of reading literacy is also a key factor in students' success in participating in learning activities. However, students' reading literacy skills still need to be continuously developed through various engaging activities tailored to their needs and characteristics. One such effort is the Read Aloud Program, which involves reading texts or stories aloud, involving active interaction between teachers and students. Through this activity, students not only gain a better understanding of the content of the reading, but also develop vocabulary, listening skills, and interest in reading. This study aims to describe the implementation of the Read Aloud Program in an effort to improve the reading literacy of third-grade students at MI Lantaburo, Tangerang City. This study uses a qualitative approach with descriptive methods to obtain an in-depth overview of the program's implementation. Informants in the study included the principal, third-grade teachers, and third-grade students at MI Lantaburo, Tangerang City. Data collection was conducted through observation, interviews, and documentation. Furthermore, the collected data were analyzed through data reduction, data presentation, and conclusion drawing.